2004
DOI: 10.1111/j.0031-9317.2004.00295.x
|View full text |Cite
|
Sign up to set email alerts
|

Responses induced by high concentration of cadmium in Phragmites australis roots

Abstract: Cadmium is an important environmental pollutant with high toxicity to plants. We report the effects of high-dose Cd (100 micro M for 21 days) on the root apparatus of Phragmites australis plants, which are characterized by elevated water detoxification capacity and widely used in phytoremediation programmes. The examination of root sections by light and electron microscopy failed to reveal any significant cadmium-induced structural or ultra-structural modifications. However, histochemical localization of Cd di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
81
0
8

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(96 citation statements)
references
References 71 publications
(81 reference statements)
7
81
0
8
Order By: Relevance
“…TBARS were identified by visible spectrophotometry as detailed in previous studies (Ederli et al, 2004), with results expressed in terms of malondialdehyde (MDA) equivalents (Kwon and Watts, 1964;Ederli et al, 2004).…”
Section: Physiology Of P Alpinummentioning
confidence: 99%
“…TBARS were identified by visible spectrophotometry as detailed in previous studies (Ederli et al, 2004), with results expressed in terms of malondialdehyde (MDA) equivalents (Kwon and Watts, 1964;Ederli et al, 2004).…”
Section: Physiology Of P Alpinummentioning
confidence: 99%
“…On the other hand, spatially localized changes in CW modification such as crosslinking or lignification are involved in the inhibition of root growth but may facilitate root acclimation to drying or toxic environment (Fan et al 2006). CW lignification and suberization of epidermis and exodermis in the RT of Phragmites australis are interpreted as a defence reaction that limits the entry of toxic metals into the roots (Ederli et al 2004). It has been reported that the two times higher lignin deposition was detected into the root endodermis in hyperaccumulator Thlaspi caerulescens in comparison to Arabidopsis thaliana (van de Mortel et al 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Especially, under Cu excess, a metal concentration-dependent increase in MDA+HAE content was observed (Skórzyñska-Polit et al 2004b) but in Phaseolus coccineus plants treated with Cd this kind of lipid oxygenation was limited (Skórzyñska-Polit and Krupa 2005). Similarly, no peroxidation was noticed in Cd-exposed plants and hairy roots of Daucus carota (Sanita di Toppi et al 1999) and in roots of Phragmites australis (Ederli et al 2004).…”
Section: Lipid Peroxidation In Plants Under Heavy Metal Stressmentioning
confidence: 91%